Bioactivity of Dental Restorative Materials: FDI Policy Statement - Gottfried Schmalz; Reinhard Hickel; Richard Bengt Price; Jeffrey A. Platt (Elsevier, 2023)
ABSTRACT: The term bioactivity is being increasingly used in medicine and dentistry. Due to its positive connotation, it is frequently utilised for advertising dental restorative materials. However, there is confusion about what the term means, and concerns have been raised about its potential overuse. Therefore, FDI decided to publish a Policy Statement about the bioactivity of dental restorative materials to clarify the term and provide some caveats for its use in advertising. Background information for this Policy Statement was taken from the current literature, mainly from the PubMed database and the internet. Bioactive restorative materials should have beneficial/desired effects. These effects should be local, intended, and nontoxic and should not interfere with a material's principal purpose, namely dental tissue replacement. Three mechanisms for the bioactivity of such materials have been identified: purely biological, mixed biological/chemical, or strictly chemical. Therefore, when the term bioactivity is used in an advertisement or in a description of a dental restorative material, scientific evidence (in vitro or in situ, and preferably in clinical studies) should be provided describing the mechanism of action, the duration of the effect (especially for materials releasing antibacterial substances), and the lack of significant adverse biological side effects (including the development and spread of antimicrobial resistance). Finally, it should be documented that the prime purpose, for instance, to be used to rebuild the form and function of lost tooth substance or lost teeth, is not impaired, as demonstrated by data from in vitro and clinical studies. The use of the term bioactive dental restorative material in material advertisement/information should be restricted to materials that fulfil all the requirements as described in the FDI Policy Statement.